Linear and undulating resistance training programming induce similar outcomes on physical fitness in elderly women - Surama do Carmo Souza da Silva; Flavio de Oliveira Pires; Marifran Tomé Batista Junior; Larissa de Lourdes Padilha Serra; Carlos Brendo Ferreira Reis; Leudyenne Pacheco de Abreu; Paula Tâmara Vieira Teixeira Pereira; Christian Emmanuel Torres Cabido; Richard Diego Leite (Revista Brasileira de Cineantropometria e Desempenho Humano)
The aim of the present study was to analyze the effect of two different types of resistance training programming (linear and daily undulating) on submaximal strength and functional capacity in elderly women. Twenty-two participants (64 ± 3 years) were randomly assigned to 2 training groups: linear programming (LP; n=12) and daily undulating programming (DUP; n =10). Functional capacity and submaximal strength (10RM) were analyzed before and after 12 weeks of resistance training. The results demonstrated improvement on strength and functional capacity after the resistance training period (p ≤ 0.05), except for the Bench Press (p = 0.30), for both groups DUP and LP. The Effect Size was, respectively, high for DUP (timed up and go test = -2.07, and timed sit test= 4.69), and high for LP (horizontal leg press = 2.35). For all other results, the effect size was trivial or small. No statistical difference was observed between programming models. The LP and DUP trainnings have similar results in increasing submaximal muscle strength in elderly women inexperienced in RT after 12 weeks of intervention (p ≤ 0,05). However, DUP appears to be more effective in increasing functional capacity. In practice, the professional can use both the LP and the DUP to improve the level of fitness in the early stages of training in this population. However, when the goal of programming is to increase functional capacity, DUP can be prioritized.